Rearrangement Heritage Peneleh Region - Ni Komang Indra Mahayani; Nyoman Ratih Prabandari; Made Mas Surya Wiguna (Architectural Research Journal, 2022)
There are many heritage buildings from the colonial era in Surabaya. Heritage building want to be used tourism attraction. The problem now is the process of urban space design was not optimal. Settlement Building has not a been regulated. Density of population make air pollution and decrease green area. Pedestrian space is not feasible, even circulation and parking are not available. There are many streets vendor sellers above the highway to impede the traffics vehicle. The purpose of the existing problems will be revived in the heritage building's, produce a quality environment and create green area. Rearrangement of the Peneleh area will be made heritage tourism become worthy and can benefit to the next generation. Theory that will be used next is the circulation and parking, open space, pedestrian ways, activity support and signage there in urban design process by Hamid Shirvani. Method used in the research naturalistic paradigm. Qualitative strategy method because it can identify physical and non-physical aspects by observ and documentation exist activity and conditions. Using primary and secondary data tactics. Results this paper there is arrange and design Peneleh area, of the structured to revive existing potential to become heritage tourism.